Analisis Penggunaan Eufemisme dalam Film Buya Hamka Vol.1 dan Vol.2 - Fatihah, Anisa Rahmani; Nusivera, Egi (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
Language plays an important role as a means of communication and reflection of culture and human thinking. In the development of language, euphemism is a form of language style used to convey meaning in a subtle and polite way so as not to offend feelings. The method used in this study is descriptive qualitative. This method involves collecting library data, reading, and recording relevant data and research materials in the Buya Hamka Vol.1 and Vol.2 films. This research is not tied to a particular place, because this study uses film objects that can be watched via the netflix application, and the time of this research was conducted for one semester. This study uses data in the form of words and sentences in the Buya Hamka Vol.1 and Vol.2 films.The data technique used is the listening and recording technique and documents in the form of images. The listening and recording technique can be done by listening to the Buya Hamka Vol. 1 and Vol. 2 films. The data analysis technique in this study is dialogue between characters to find out the forms of euphemism from the Buya Hamka Vol. 1 and Vol. 2 films. The results of the data found were 25 data in 5 forms of euphemism. This study focuses on the form and meaning of euphemism in the film Buya Hamka Vol. 1 and Vol. 2. This study aims to analyze the form and meaning of euphemism that appears in the film.